KAISAR AMERIKA DI NEGERI SAKURA : PERANAN DOUGLAS MACARTHUR DALAM REKONSTRUKSI JEPANG PASCA PERANG DUNIA II - Ginanjar Setia Mulyana; Agus Mulyana; Leli Yulifar (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2017)
The main purpose of this research is to describe the Role of Douglas MacArthur in the Reconstruction of Japan after World War II in 1945-1951. Historical method is being used in this research paper, the method consists of : heuristic, critic, interpretation, and historiography. While the main topic of this research is how is the role of Douglas MacArthur in the reconstruction of Japan after World War II. Since he was appointed as SCAP in Japan by president Truman, with the supreme authority more than the Emperor himself, the U.S military officer made many reconstructive policies for Japan which was U.S main enemy of the Pacific War. With so many critics threw upon him from the Western countries, MacArthur rebuilt Japan from the political and economical sector with some changes especially liberalism and democratic view. The purpose of the reconstruction in to make Japan as the same side with the United States in the middle of Cold War with Soviet Union.